Toward a Positive hiv Theology: A Queer Hermeneutic Reading of the Book of Job - Torres, Cruz Edgardo; Quero, Hugo Cordova (2024)
This article aims to trace the history of hiv/aids in Central America, with particular attention to El Salvador. Its first section presents a periodization that details the evolution of the response and understanding of the region in the social context. The second section focuses on a detailed periodization of how faith communities reacted to the presence of hiv/aids, especially highlighting their responses to the affected people. The third section of the article provides a biblical, theological, and pastoral perspective from the early days to the current response of faith communities to hiv/aids.
Keywords: HIV/AIDS; Pastoral Theology; Book of Job; queer hermeneutics; Queer theologies